Pemanfaatan Precipitated Calcium Carbonat dari Batu Kapur dalam Pembuatan β- TCP sebagai Bahan Dasar Implan Tulang - Noor Isnaini Azkiya; Fanny Prasetia; Rosita Dwi Chrisnandari; Wianthi Septia Witasari (Politeknik Negeri Malang, 2021)
One of the biocompatible materials that are often used as a basic materials for bone and dental implants is tricalcium phosphate. This material can be produced from precipitated calcium carbonate (PCC) limestone because it has a very high calcium content. The method used to synthesize tricalcium phosphate was deposition of CaO and H3PO4 precursors in ethanol media. The results of the synthesis was characterized using FT-IR instruments, AAS, UV-Vis spectroscopy, and XRD. Based on the results of the UV-Vis spectroscopic analysis, the Ca/P ratio of the synthesis results obtained was 1.87. FT-IR test showed the presence of a Ca-O group at wave number 1400 cm-1 and PO43- group at wave numbers 561 cm-1 and 1041 cm-1. XRD test showed highest peaks of β-TCP (tricalcium phosphate) according to JCPDS no. 09-0169.